Accuracy of HRCT Chest in Diagnosis of Covid-19 Pneumonia Against Reverse Transcription Polymerase Chain Reaction (Medical Forum Monthly, 2021)
Objective: To assess the accuracy of high-resolution computed tomography of chest for diagnosis of pneumonia related to corona virus disease taking Reverse transcription polymerase chain reaction as gold standard.Study Design: Cross Sectional surveyPlace and Duration of Study: This study was conducted at the Jinnah Medical Diagnostic Center, Sialkot Pakistan, for 6 months from 1st April 2020- 30th September 2020.Materials and Methods: 200 patients were included with symptoms of coronavirus pneumonia were included. HRCT chest was done and findings were recorded. Then RT-PCR assays was applied and findings were recorded. Patients were labeled as positive or negative. Data was analyzed using SPSS v.20. Diagnostic accuracy of HRCT Chest was calculated taking RT-PCR as gold standard.Results: The mean age of patients was 35.69 ± 12.95 years. There were 103 (51.5%) males and 97 (49.5%) females. On HRCT Chest, 121 (60.5%) had ground glass appearance and 108 (54%) had consolidation. The sensitivity of HRCT Chest was 70.1%, specificity was 60.3%, positive and negative predictive values were was 79.3% and 48.1% and diagnostic accuracy was 67%.Conclusion: HRCT Chest is highly accurate to diagnose the COVID-19 in symptomatic patients and can replace RT-PCR which is expensive than HRCT Chest and not readily available in all set-ups.